Centre d'Art Contemporain Fri-Art Kunsthalle 2001 - 2002. - Antille, Emmanuelle; Fleury, Jean Damien; Hanru, Hou; Ritter, Michel; Steinauer, Jean; Zürcher, Sarah; de Weck, Jean-Baptiste; Fri-Art Centre d'Art Contemporain Kunsthalle, Fribourg (Fribourg : FRI-ART Centre d'Art Contemporain - Kunsthalle, 2002)
Wang Du ; Kusolwong Surasi ; Meese, Jonathan ; Chang, Patty ; Korine, Harmony ; Lamelas, David ; Baeriswyl, Bruno ; Sidler, Jacques ; Dafflon, Stéphane ; Berclaz, Jean-Daniel ; Buser, Renate ; Antille, Emmanuelle ; Carron, Valentin ; Parrino, Steven ; Ban, Shigeru ; Mockbee, Samuel ; Rakowitz, Michael ; Busslinger, Erich ; Draeger, Christoph ; Berdaguer & Péjus ; Atelier Bow-Wow ; Yung Ho Chang ; Tsuyoshi Ozawa ; Baeriswyl, Boris ; Baudevin, Francis ; Fahrlaender, Adrian ; Fleury, Jean Damien ; Glaisen, Sarah ; Hamacher, Christiane ; Laubscher, Eliane ; Lovay, Chistiane ; Marbacher, Vincent ; Marti, Yves ; PAC ; Pythoud, Jean ; Ritter, Michel ; Significans ; Spalinger, Nika ; Török, Stefano ; Walker, René ; Auderset ; Angèle ; Chofflon, Eliane ; Fracheboud, Albert ; Morandi, Raymond ; Nello ; Piguet, Henri ; Berset, Nicolas ; Capeder, Gion ; Cotting, Laurence ; Krieg, Isabelle ; Paulus, Lauris ; Philipona, Didier ; Savary, Nicolas ; St-Denis@ ; Tendon, Hugo ; Neshat, Shirin ; Winter, Wolfgang ; Hörbelt, Berthold
Engels & Frans
boek